Letters to the Editor—Extension of Dantzig's Algorithm to Finding an Initial Near-Optimal Basis for the Transportation Problem - Russell, Edward J. (Operations Research, 1969)
This note presents a new method for finding a starting basis for transportation problems; it produces a near-optimal basis, and appears to be superior to present methods.